Event studies : theory and management for planned events - Getz, Donald, 1949- (Events management series, 2024)
Fully updated and revised in its fifth edition, Event Studies remains the most comprehensive book devoted to developing knowledge and theory about event management and event tourism, focusing on the study of events, the event experience, and meanings associated with them. International in scope and embellished with useful figures and tables throughout, the authors carefully examine current forces, trends, and issues, including impacts of the pandemic. All the major types of planned events are profiled, with emphasis on their forms, functions, experiential dimensions, meanings, and values. This book’s framework encompasses antecedents, planning and design, outcomes and impacts, and the various patterns and processes that influence the events sector, including policy.